Hydrogeological appraisal of basement and sedimentary terrain in Ogun state using Geoelectrical methods - Adegoke Ige, Aladeboyeje; Joseph Olakunle, Coker; Okechukwu Ebuka, Agbasi; Namdie Joseph, Inyang (International Journal of Advanced Geosciences, 2020)
The coverage of the groundwater potential was estimated using the geometry calculator, the potential groundwater zones were validated using geophysical surveyed points of some selected locations in Abeokuta and Ewekoro. Generally, the result of the study shows that the higher the aquifer thickness and depth the better the groundwater potential. In the basement part of the study area (Abeokuta), the Northwestern region is characterized by increase in overburden thickness (28.1â€¯m at VES-9), weathered layer resistivity (546â€¯â„¦â€¯m at VES-7) and longitudinal conductance unit (0.193â€¯S at VES-3 and 0.218 S at VES-7), reflecting high aquifer potentials. In this regard, the Northeastern part of the study area can be categorized as good groundwater potential; moving towards the Southwestern part from the northern, groundwater potentiality changes from good to moderate while the Southwestern/ central part is categorized as area with poor groundwater potential. In the Sedimentary part of the study area (Ewekoro), the northcentral region is characterized by increase in overburden thickness (93â€¯m at VES-10), longitudinal conductance unit (3.644â€¯S at VES-6), reflecting high aquifer potentials. In this regard, the northcentral part of the study area can be categorized as good groundwater potential; moving towards the northeastern part of the study area, groundwater potentiality changes from good to moderate while the southwestern part is categorized as area with poor groundwater potential. The area showed very good protective capacity at VESâ€™s 2, 3, 4, 5, 7 and 8; making 60% of the VES stations. Good protective capacity is observed at VES 1 and 6, making 15% of the VES stations in the town. The excellent protective capacity is observed at VES 9 and 10; making 15% of the study area.Â Â Â